(untitled) (Development Service Industry Management, 2024)
The article reveals a scientific vision of ways to improve the functional activities of local self-government bodies in terms of business development in the context of decentralization of public power in Ukraine. Goal of the article is to substantiate the significance of the functional activities of local self-government bodies with regard to business development in the context of decentralization of public power in Ukraine and to improve them with due regard to existing problems and new challenges. Research methods: to substantiate the importance of improving the functional activities of local governments in terms of business development in the context of decentralization of public power in Ukraine, the systemic and structural approaches, the method of analysis and synthesis, the statistical method, and the generalization of conceptual provisions on the studied issues presented in the work of scientists were used. The author argues that the process of functional optimization of local self-government bodies’ (LSG) activities related to business development should be public, based on clear legal norms, and focused on obtaining a positive effect for the State, territorial community, business structures, and the population. It is stated that business is a system which is influenced by many factors (legislative influence, infrastructure provision, etc.), business development is a process which is intertwined with other processes at the level of a territorial community, region, and the State (socio-economic, information and communication, etc.), and business organizations, together with local self-government bodies and other stakeholders, are the subjects of management of territorial community development. It is emphasized that the functional and authorized activities of local self-government bodies in relation to business development in the context of decentralization of public power in Ukraine do not exist in a “pure” form, but are closely interrelated and are manifested in other types of such activities, for example, in relation to socio-economic development, health care, environmental protection, social protection of the population, etc. It is emphasized that since local self-government bodies are public sector organizations and their activities are aimed at producing public goods, their functional activities should be improved in terms of stimulating business development in the communication area and in the area of increasing the personal responsibility of business structures to society (for “closing” important information from society, environmental pollution, etc.). It is proved that the war in our country causes risks in many areas and activities, including investment, and therefore, local governments should implement functions to stimulate investment activity in territorial communities to ensure their economic development (incentives, grants, etc.). It is determined that a separate important area of the functional activities of local self-government bodies should be to support veteran business by: improving the necessary regulations; implementing programs to support veterans and their families to create their own businesses; creating an information and educational infrastructure for the development of entrepreneurial initiatives of war veterans, etc.